(untitled) (Journal of Parents and Teachers, 2014)
The following article deals with some sociologic, psychologic, epistemological and pedagogical criteria to take decisions. It offers a different perspective, with examples for every decision. In addition, it talks about ten related criteria to curricular project start up, which it is an essential element in school.